Aphids of Iran: their host plants and distribution - Mehrparvar, Mohsen (Zootaxa, 2024)
A reviewed checklist of aphids (Hemiptera: Sternorrhyncha: Aphidomorpha) species recorded in Iran is presented as a catalogue in alphabetical order considering recent taxonomic changes. In total, 572 species along with 29 subspecies within 148 genera, belonging to 13 subfamilies, 3 families and 3 superfamilies of Aphidomorpha are presented. In addition, the list of host plants and distribution of the aphid species in Iran and the related references are provided.